Убиството на Гоце Делчев во странскиот печат (мај-јуни 1903 г.) - Минов, Никола (Здружение на историчарите на Република Македонија, 2019)
In this paper we present and analyze articles from over 100 newspapers worldwide, reporting on the death of the most prominent leader of the Internal Macedonian Revolutionary Organization – Gotse Delchev – in a skirmish with the Ottoman forces near the village of Banitsa. The presented articles were originally published in May and June 1903 in Great Britain, Austria-Hungary, France, Italy, Germany, the Russian Empire, the Netherlands, Sweden, Denmark, Greece, Spain, Switzerland, USA, Australia and New Zealand.
Keywords: Gotse Delchev, Banitsa, newspapers